A unique and discrete Ce(iii) macrocyclic complex exhibits ferroelectric, dielectric, and slow relaxation of magnetization properties. Issue 10 (7th April 2022) - Wasim, Mohd; Ansari, Kamal Uddin; Kumar, Pardeep; Mallick, Binit; Shanmugam, Maheswaran
Abstract : A [Ce(L1)(NO3 )3 ] (1 ) was found to exhibit ferroelectric and magnetic bistability simultaneously. The ferroelectric to paraelectric transition was observed at 303 K and a small external electric field was required to switch the spontaneous polarization in 1 . Abstract : A discrete [Ce(L1)(NO3 )3 ] (1 ; L1 = macrocyclic Schiff base ligand) complex exhibits both ferroelectricity and magnetic bistability together, which is extremely rare and challenging to achieve. The presence of the Second Harmonic Generation (SHG) signal in 1 implies the presence of a non-centrosymmetric space/point group associated with this complex. The ferroelectric phase transition temperature in 1 is observed at room temperature (303 K), which is confirmed by dielectric measurements. Switching the spontaneous polarization in 1 requires a low external electric field (2 V). The presence of magnetic bistability in 1 was confirmed by the frequency-dependent out-of-phase susceptibility signals ( H dc = 1.5 kOe) and the effective energy barrier for the magnetization reversal is estimated to be 29.04 K. Therefore 1 is envisaged as a potential molecular-based multiferroic and can be considered for low power memory applications.